PENGALAMAN PROSES PEMBELAJARAN JARAK JAUH DI PERGURUAN KEAGAMAAN ISLAM NEGERI: DAMPAK PANDEMI COVID-19 - Slamet Slamet (STAI Ma'had Aly Al-Hikam Malang, 2021)
The Covid-19 pandemic has wholly changed all aspects of life, including the learning system in higher education. So that the learning process must be carried out with a total distance education model, in its implementation, it is not accompanied by good planning. The main purpose of this study is to describe and examine the differences in the experiences of lecturers and students in carrying out the learning process with the distance education model as the impact of the Covid-19 Pandemic. This research was conducted using a descriptive quantitative approach and a different test. The research instrument is a questionnaire designed based on distance education theory. The measurement scale uses a Likert scale (1=strongly disagree to 5=strongly agree). Data were collected through surveys to lecturers and students. Due to the Covid-19 pandemic, the questionnaire was designed in a Google Form and distributed through the WhatsApp Group of colleagues at several Islamic Universities in Indonesia. The number of respondents collected was N=527 (n=123 lecturers and n=404 students). Before data analysis, data were edited, and the result was that all data were declared valid. Data analysis used the Categorization Index and a different test with the Independent-Samples Kolmogorov-Smirnov Test approach. The results of the descriptive research show that the learning process using the distance education model, from the experience of the lecturers, is stated to be less effective and even tends to be ineffective. Student experience also shows the same thing, which is less effective, and the small number of many students say it is effective. The difference in experience in the learning process with the distance education model between lecturers and students is different. This difference is caused by the habit between lecturers and students using information technology devices as a medium in distance education that is not the same.